International trade and tax-motivated transfer pricing - Ansgar F. Quint; Jonas F. Rudsinske (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2020)
We study the welfare and distribution effects of corporate taxation and transfer pricing in an asymmetric general oligopolistic equilibrium trade model. Without profit shifting, an increasing profit tax rate shifts welfare towards the taxing country, where it also decreases real wages, whereas real wages rise in the other country. Labor income increases relative to profit income in both countries. Transfer pricing generates an additional benefit from exporting, such that companies want to expand production. Caused by this supply channel, real wages will rise in both countries. Due to shifting tax incomes, a cross-country demand channel relocates consumption from the high- to the low-tax country. In the low-tax country, real profits decrease such that the labor share of income rises.
Keywords: E25; F10; H25; H26; L13; 330; general oligopolistic equilibrium; international trade; labor share; profit shifting; tax evasion; transfer pricing